Geographic Spillover Effects of Regional Funds and their Impact on the European Convergence Process over 1989-1999 - Sandy Dall'erba; Julie Le Gallo (European Regional Science Association (ERSA), 2003)
The aim of this paper is to highlight the role of geographic spillover effects due to the regional funds on the convergence process of 145 European regions over 1989-1999. With the aim of enhancing cohesion, these funds are primarily allocated to the least developed regions. First the most important part of these funds is devoted to transportation infrastructures, which induce strong spillover effects. However they do not necessarily contribute to a more even regional development. Their impact has therefore to be seen in the light of growth rate variations of the targeted region and of the whole sample. Second, since the wealthiest regions have more ability to accompany regional funds, the role of additional funds in the regional development process is investigated as well. Using the formal tools of spatial econometrics, we first detect strong evidence of spatial autocorrelation, both on per capita GDP and regional funds. Moreover, two clusters, representative of the core-periphery framework, are persistent over the period and highlight spatial heterogeneity. These spatial effects are then included in the estimation of an appropriate conditional -convergence model, which allows us to control for spatial spillover effects among regions. Finally, with this model, we assess the impact of European regional funds on the regional convergence process using simulation experiments.
Keywords: 330